N6-Isopentenyladenosine Enhances the Radiosensitivity of Glioblastoma Cells by Inhibiting the Homologous Recombination Repair Protein RAD51 Expression - Navarra, Giovanna; Pagano, Cristina; Pacelli, Roberto; Crescenzi, Elvira; Longobardi, Elena; Gazzerro, Patrizia; Fiore, Donatella; Pastorino, Olga; Pentimalli, Francesca; Laezza, Chiara; Bifulco, Maurizio (Frontiers in Oncology, 2020)
Glioblastoma is among the most common malignant brain tumors and has a dismal prognosis due to the poor response to therapeutic regimens such as ionizing radiation and DNA-alkylating agents. In our study, we investigated the radiosensitizing activity of the N6-isopentenyladenosine (iPA), an naturally modified adenosine harboring an isopenenyl moiety, which shows antiproliferative effects on glioblastoma cell lines. We observed that co-treatment with ionizing radiation and iPA at micromolar concentration inhibited colony formation and viability of glioblastoma cell lines but not of non-malignant human cells. The combined treatment significantly attenuated the repair of radiation-induced DNA damage by inhibiting both the expression and irradiation-induced foci formation of RAD51, a key player in the homologous recombination repair process, leading to persistent DNA damage, as reflected by an increase of γ-H2AX foci. The radiosensitizing effect relied also on the inhibition of STAT5a/b activation, which is crucial for RAD51 expression, suggesting that iPA modulates the STAT5a/b-RAD51 axis following exposure to ionizing radiation. Overall, these data suggest that iPA, by acting through RAD51 inhibition at the mechanistic level, could function as a promising radiosensitizing agent and warrants further evaluation in prospective clinical trials.